Arabic words in medieval literary monument of Saif Saray "Gelston beat-Turki" - Alzhanbaeva, U; Seitmetova, J (Journal of Oriental Studies, 2016)
This article discusses the lexico-grammatical description of Arabic words in medieval literary monument of Saif Saray "Gelston beat-Turki". Defines the number of Arabic words in the monument, identified the phonetic, grammatical and semantic changes.